PERAN MAJELIS ULAMA INDONESIA (MUI) DALAM BIDANG PENDIDIKAN - Mukhyar Mukhyar; Maskur Rosyid (stit-islamic-village, 2020)
This paper wants to see the other side of the role of various elements of society in contributing to nation-building. The acceleration of development is not solely the responsibility of the government as the holder of government administrative authority and state administration, but it is the joint responsibility of the whole community, including the Indonesian Ulama Council (MUI). In the context of education, MUI has contributed significantly in transforming the various developments of the times to contribute to improving the quality of Indonesian human resources. For example, MUI provides full support for equality of religious education and pesantren with public education institutions, provides full support for the existence of religious education institutions through the umbrella of the law, encouraging full strengthening and development of basic character education in educational institutions. From the various roles of the MUI in the development of education, it can be concluded that the greater the role of the MUI in the field of education, the more qualified Indonesian human resources are.